P-028 First year results of merci embolectomy in Japan. (12th July 2011) - Sakai, N; Minematsu, K; Hasegawa, Y; Ogasawara, K; Saito, N; Taki, W
Abstract : Background and Significance: The Merci Retriever has been used at US stroke centers for mechanical embolectomy in acute stroke since 2004. Until very recently, however, there were no approved devices in Japan for mechanical embolectomy in acute stroke. The Merci Retriever was the first device to obtain such approval and was introduced into clinical practice in late 2010. Methods: A condition of approval in Japan is that every patient treated with the Merci Retriever must be prospectively entered into a post-market study. Key data elements include baseline demographic and medical history, IV rt-PA received or not, procedural details, in-hospital follow-up and 90 days clinical status. Clinical outcomes at discharge and 90 days were obtained prospectively with good outcomes defined as modified Rankin Score ≤2. Recanalization was reported using the TICI classification, with 2a, 2b and 3 considered as success. Results: 110 patients submitted from 14 centers between July 2010 and February 2011. Median patient age and NIHSS were 72 and 18, respectively and 68% were male, similar to prior clinical studies of the Merci Retriever (MERCI, Multi MERCI, and Merci Registry). Median time from last seen at baseline to treatment onset was 4 h. IV lytic was used in 42%. Successful recanalization (TICI 2a/2b/3) was achieved in 74% of cases, with 48% achieving TICI 2b or 3. Symptomatic subarachnoid hemorrhage occurred in 3.8% and intracerebral hemorrhage in 2.9% of cases. In-hospital death is 13.5% and 25.8% of patients were discharged from the hospital with a good outcome (mRS=0–2). Data collection and entry is on-going and the latest data will be reported at the time of presentation, including 90 days clinical outcomes. Conclusions: Mechanical embolectomy with the Merci Retriever is being rapidly adopted in Japan. This is the first report of procedural and clinical outcomes from mechanical embolectomy in Japan. The preliminary results are similar to those obtained in previous prospective pivotal and post-marketing studies in the USA. Our findings suggest that the rates of revascularization, good clinical outcomes and mortality in initial clinical practice in Japan are comparable to those observed in MERCI, Multi MERCI, and the post-marketing Merci Registry.